2005
DOI: 10.1007/s00066-005-1272-3
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Treatment Including Postoperative Radiation and Concurrent Chemotherapy with Weekly Docetaxel is Feasible and Effective in Patients with Oral and Oropharyngeal Cancer

Abstract: Concurrent radiation and chemotherapy with weekly docetaxel is a feasible postoperative treatment in a multimodality approach to oral and oropharyngeal cancer, resulting in high overall and disease-free survival. This approach warrants further evaluation in prospective randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 36 publications
(41 reference statements)
2
25
0
5
Order By: Relevance
“…These results are at the top end of the results published by others. 8,[20][21][22][23] It is difficult to compare our survival results with the literature as study groups vary with regard to number of patients, tumor stage, and treatment modality. Furthermore, treatment modalities concerning radiochemotherapy changed, especially since 2002, when the IMRT technique for radiotherapy started to be used.…”
Section: Discussionmentioning
confidence: 99%
“…These results are at the top end of the results published by others. 8,[20][21][22][23] It is difficult to compare our survival results with the literature as study groups vary with regard to number of patients, tumor stage, and treatment modality. Furthermore, treatment modalities concerning radiochemotherapy changed, especially since 2002, when the IMRT technique for radiotherapy started to be used.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent RCT is now used in a variety of different tumors [9,10,14]; but how can this treatment benefit patients with comorbid conditions? Simultaneous RCT resulted in partial or complete remission in 74% of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, randomized studies have demonstrated the superiority of radiotherapy in combination with chemotherapy over radiotherapy alone. RCT with multiagent chemotherapy, or with hyperfractionated radiotherapy, may lead to even better outcomes, although toxicity may be increased [2,3,8,11,14,15,17,18,20,22,25,32].…”
Section: Discussionmentioning
confidence: 99%